For My Studies, I Wouldn't Say No: Barriers to, and Opportunities for, Higher Education for Syrian Refugees in Jordan - Goldberg, Ilana B. (Tufts Archival Research Center, 2020)
This thesis uses personal interviews to explore the barriers to, and opportunities for, higher education for Syrian refugees in Jordan in light of the ongoing conflict in Syria that began in 2011. Advisor: Professor Jayanthi Mistry.